2004
DOI: 10.1242/dev.00986
|View full text |Cite
|
Sign up to set email alerts
|

Segmental development of reticulospinal and branchiomotor neurons in lamprey: insights into the evolution of the vertebrate hindbrain

Abstract: Materials and methods EmbryosMature male and female lampreys, Lethenteron japonicum, were collected in a tributary of the Miomote River, Niigata, Japan, during the breeding season (early June). The eggs were artificially fertilized and maintained in 10% Steinberg solution (Steinberg, 1957) at 20°C. Embryonic stages were assessed morphologically according to the sequence established by Tahara (Tahara, 1988) for L. reissneri, a brook lamprey species closely related to L. japonicum. Retrograde labeling of hindbra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
115
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 103 publications
6
115
0
Order By: Relevance
“…The pTRG is intrinsically rhythmically active and glutamatergic, and projects to vagal motor neurons (Cinelli et al, 2013), features shared with the Xenopus DTAM vocal circuit (reviewed in Zornik and Kelley, 2017). Both the pTRG and DTAM are located in the rostral hindbrain compartment derived from embryonic rhombomere 1 (r1; Murakami et al, 2004;Morona and González, 2009). The several shared features described above support the homology of DTAM to the pTRG.…”
Section: Evolution Of Hindbrain Circuits What Is Dtam? Hindbrain Circmentioning
confidence: 99%
“…The pTRG is intrinsically rhythmically active and glutamatergic, and projects to vagal motor neurons (Cinelli et al, 2013), features shared with the Xenopus DTAM vocal circuit (reviewed in Zornik and Kelley, 2017). Both the pTRG and DTAM are located in the rostral hindbrain compartment derived from embryonic rhombomere 1 (r1; Murakami et al, 2004;Morona and González, 2009). The several shared features described above support the homology of DTAM to the pTRG.…”
Section: Evolution Of Hindbrain Circuits What Is Dtam? Hindbrain Circmentioning
confidence: 99%
“…Within the HB, which in vertebrates is both morphologically and molecularly subdivided into rhombomeres (Lumsden and Krumlauf, 1996), AP patterning is generally controlled by a hox code involving nested collinear expression of hox genes along the AP axis, which defines the identity of each rhombomere (Trainor and Krumlauf, 2001). It is well established that RA regulates this collinear expression of hox genes in the vertebrate HB (Glover et al, 2006;Murakami et al, 2004). Treatments with RA induce an anterior expansion of the HB and the spinal cord (SC) and inhibit formation of anterior brain structures, such as the forebrain (FB) and the midbrain (MB) (Durston et al, 1989).…”
Section: Patterning Of the Central Nervous System And Neuronal Differmentioning
confidence: 99%
“…This concurs with the fact that targeted mutation of Hoxa2 in mice leads to partial duplication of the lower jaw at the expense of the normal BA2 skeleton (the hyoid cartilage) (Gendron-Maguire et al, 1993;Rijli et al, 1993;Kanzler et al, 1998;Ohnemus et al, 2001). In the lamprey (Lampetra fluviatilis), a jawless vertebrate, the forepole of the embryo does not express Hox3 (Murakami et al, 2004), whereas, as observed by Cohn (Cohn, 2002), the HoxL6 gene (the lamprey homologue of vertebrate Hoxb6) does not obey the colinearity rule (between Hox gene organisation in the chromosome and the anterior limit of their expression in the embryo). The HoxL6 expression domain reaches the rostral-most part of the embryo.…”
mentioning
confidence: 95%
“…In the lamprey (Lampetra fluviatilis), a jawless vertebrate, the forepole of the embryo does not express Hox3 (Murakami et al, 2004), whereas, as observed by Cohn (Cohn, 2002), the HoxL6 gene (the lamprey homologue of vertebrate Hoxb6) does not obey the colinearity rule (between Hox gene organisation in the chromosome and the anterior limit of their expression in the embryo). The HoxL6 expression domain reaches the rostral-most part of the embryo.…”
mentioning
confidence: 95%